Produto interno bruto ajustado ambientalmente para Amazônia legal brasileira: uma análise de matriz de insumo-produto e matriz de contabilidade social - Brasileiro, Andrea Castelo Branco (2012)
The purpose of this work was to present and apply an analytical tool to the flows of goods and income between economic agents and the environment that allows us to calculate the Environmental Gross Domestic Product (EGDP) for Brazilian Legal Amazon. In order to achieve this goal the Environmental Social Accounting Matrix (ESAM) was developed. The model was developed from the traditional Social Accounting Matrix, the Environmental Input-Output Analysis Models, and from the United Nations handbook on the System of Integrated Environmental and Economic Accountings. The EGDP was calculated from the Environmental Input-Output Analysis, since the unavailability of data did not allow the application of the model of ESAM. The flows between the economy and the environment considered were the emissions of green house gases (depreciation of natural capital) and the investment needed to return the air to the same quality it had before being polluted. The results showed that the inclusion of depreciation of natural capital in the Gross Domestic Product (GDP) and in the added value (AV) calculation for each industry of the Brazilian Legal Amazon Region diminished the AV significantly in the industries of cattle (235%), soybean (77%), and other activities of livestock and agricultural (24%). In the Rest of Brazil, the industries with the highest impact of depreciation of natural capital on AV were soybean (30%), cattle (15%) and sugarcane (13%). The total EGDP of the Brazilian Legal Amazon Region was 15% smaller than its total GDP, whereas this difference for the rest of Brazil was 1%. Considering that the GDP is a component of economic wellbeing, the results show a significant reduction in economic wellbeing due to green house gas emissions released into the air by economic activities, mainly due to land use changes. The Environmental Social Accounting Matrix Model is a useful tool to help decision makers since it offers an analytical instrument for economic behavior and the impacts of economic activities on the environment.